An immunohistochemical study of TIMP-3 expression in oesophageal squamous cell carcinoma - Miyazaki, T (Nature Publishing Group, 2004)
Tissue inhibitor of metalloproteinase-3 (TIMP-3) inhibits the activity of matrix metalloproteinase, which may play an important role in carcinoma invasion and metastasis. We have investigated the relationship between TIMP-3 reduction and clinicopathological factors in oesophageal squamous cell carcinoma (ESCC). We examined tissue specimens that had been removed from 90 patients with thoracic oesophageal cancer who had undergone surgery between 1983 and 2001. Immunohistochemical staining was performed by the standard streptavidin–biotin method. Immunostaining of TIMP-3 was seen in the cytoplasm of cancer cells and normal oesophageal epithelial cells, particularly in cells located in shallow areas of the tumour. TIMP-3 preserved (+), moderate (±), and reduced (−) cases accounted for 30, 27, and 33 of the 90 patients, respectively (33, 30, 37%). Significant correlations were observed between TIMP-3 expression and depth of tumour invasion (P=0.001), number of lymph node metastases (P=0.003), infiltrative growth pattern (P=0.003), and disease stage (P=0.005). The survival rates of patients with TIMP-3 (−) cancer were significantly lower than those of patients with TIMP-3 (+) and TIMP-3 (±) cancer (P=0.0003). The mean 5-year survival rates of patients with TIMP-3 (+), (±), and (−) were 50, 58, and 21%, respectively. In conclusion, decreased expression of TIMP-3 protein correlates with invasive activity and metastasis. This makes the prognosis for patients with cancer that has lost TIMP-3 significantly less favourable than that for patients with cancer that has maintained TIMP-3.